UNIPERSONALITAS KRISTUS SEBAGAI LANDASAN UTAMA KESELAMATAN BERDASARKAN 1 TIMOTIUS 2:5-6 DAN RELEVANSINYA BAGI UMAT KRISTEN MASA KINI - Sariyanto (Institut Agama Kristen Negeri Kupang, 2026)
Misunderstandings about Christology, especially concerning the unipersonality of Christ, can weaken the core of the Christian faith. With the rise of religious relativism and secularism, many equate all religions as paths to God, which can obscure the correct understanding of Christ's role as the only mediator between God and humanity. This study aims to examine the concept of the unipersonality of Christ in 1 Timothy 2:5-6, which emphasizes that only Christ, as the sole mediator, can reconcile the relationship broken by sin. The unipersonality of Christ, which combines two natures, divinity and humanity, in one person, is the fundamental basis for the salvation of humanity. This verse affirms that salvation cannot be achieved through human effort or any other mediator, but only through the work of Christ as the perfect atonement. Therefore, the contemporary church is called to uphold this doctrine, ensuring that only through Jesus can humanity be reconciled with God, especially in light of the existing challenges.